Factors Influencing Work Shift-related Fatigue among Nurses: A Cross-Sectional Study - Yuniza, Rheyna (Inspirasi Foundation, 2025)
Introduction: Human Resource Management (HRM) in hospital settings is a comprehensive process that includes recruitment, placement, and employee development to ensure optimal healthcare service delivery. A prevalent HRM issue in hospitals is nurse work fatigue, which negatively affects performance, patient safety, and service quality. Shift work, a core aspect of hospital operations, is a major contributor to fatigue due to its impact on physical and psychological well-being. Objective: This study aimed to examine the relationship between work shift factors—specifically length of work shifts, shift changes, and shift rotations—and the level of work fatigue among nurses at Dr. H. Abdul Moeloek Regional Hospital in Bandar Lampung. Method: A quantitative, cross-sectional study was conducted with a sample of 142 nurses selected using proportional stratified random sampling. Data were collected through structured questionnaires and analyzed using statistical tests to assess the significance of associations between work shift variables and nurse fatigue levels. Result: The findings revealed significant associations between all three work shift variables and nurse fatigue. The length of work shifts (p = 0.039), shift changes (p = 0.028), and shift rotations (p = 0.049) were all significantly related to fatigue levels. Nurses with sufficient shift arrangements experienced lower fatigue than those with poor shift conditions. Conclusion: Work shift management significantly influences nurse fatigue levels. Irregular rotations and extended work hours contribute to higher fatigue, potentially compromising nurse performance and patient care. Improved shift scheduling, adequate rest, and supportive health and stress management strategies are essential to reduce fatigue and enhance nurse well-being in shift-based work environments.